Exploring EFL Students Perceptions of Online Articles for Critical Reading: Persepsi Mahasiswa EFL terhadap Artikel Online dalam Membaca Kritis - Ramadhini, Ninda Aulia; Wahyuni, Indah Fajar (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Critical reading has become an essential higher-order literacy skill in digital learning environments, where students must interpret, analyze, and evaluate diverse academic information. Specific Background: In EFL learning, online articles offer authentic digital materials that can help students understand main ideas, analyze arguments, and assess information credibility. Knowledge Gap: Although digital resources are widely accessible, students’ access to online articles does not automatically lead to deeper critical reading competence, and studies focusing on students’ perceptions remain limited. Aims: This study analyzes EFL students’ perceptions of using online articles to develop critical reading skills. Results: Data from 31 undergraduate students using a 17-item four-point Likert questionnaire showed strong internal consistency, with Cronbach’s Alpha of 0.881. Descriptive findings indicated generally favorable perceptions, with mean scores ranging from 2.81 to 3.61 in the agree category. Students viewed online articles as useful for identifying central ideas, analyzing arguments, connecting texts with prior knowledge, and evaluating information reliability. However, some students still experienced difficulty explaining the deeper meaning of reading materials. Novelty: The study highlights the digital literacy paradox in EFL learning, showing that positive engagement with online articles coexists with challenges in reflective articulation and deeper interpretation. Implications: Online articles can be integrated as authentic learning resources, but they should be accompanied by guided questioning, reflective writing, and discussion-based activities to support deeper critical expression. Highlights• Digital texts helped learners identify main ideas and evaluate information.• Respondents showed strong agreement with scaffolded analytical activities.• Deeper explanation of textual meaning remained a key learner difficulty. KeywordsEFL Students; Online Articles; Critical Reading; Digital Literacy; Reflective Thinking